Factors Influencing Birth in Adolescents in the Province of West Nusa Tenggara - Rofita, Desi; Pamungkas, Catur Esty; Amini, Aulia; Siti Mardiyah WD; Retno Dewi Puspitasari (Universitas Airlangga, 2024)
Background: Adolescent childbirth is a global problem, especially in developing countries. Based on data from the 2017 Indonesian Demographic and Health Survey (SDKI), the ASFR 15-19 at the national level is 36 per 1000 women while the NTB Province is 42 per 1000 women, so it is still in a position above the national level. Aims: To know the factors that influence teenage births. Methods: This research is an analytical study using secondary data from the results of the 2017 Indonesian Demographic and Health Survey (IDHS) by using a cross-sectional approach. The population in this study was 1368 respondents. sampling technique using purposive sampling obtained as many as 806 respondents. Data analysis was using univariate, bivariate analysis with chi-square, and multivariate with logistic regression analysis. Results: Based on the results of bivariate analysis, it was found that there was a significant relationship between the factors of education (CI 95% 2.996-16.366), age of first sex (CI 95% 2.271-11.853), use of contraception (CI 95% 0.292-0.846), number of children born (CI 95% 0.378-0.880) to teenagers. Factors of employment status (CI 95% 0.667-1.482) and living area (CI 95% 0.635-1.406) did not have a significant relationship with teenage births, while the results of multivariate analysis showed that the R2 value was 0.603 which means that education, age of first sex, use of contraceptives, and number of children contributed to teenage births of 60.3%, the remaining 39.7% is caused by other variables. Conclusion: Factors of education, age of first sex, use of contraceptives, and the number of children have a significant relationship with teenage births. It is hoped that the BKKBN of West Nusa Tenggara Province will evaluate the programs that have been established to determine the effectiveness of these programs in overcoming the problem of teenage births.